Hierofonía and cosmology in indigenous art Sibundoy Valley - Óscar Fernando Sánchez Suárez (Corporación Universitaria Minuto de Dios, 2013)
An analysis of the large existing indigenous cultural diversity in South America as the initial part of the study and support of research is presented. It is also a reflection from the perspective of different authors on the thinking of man in relation to nature, archetypes, cosmogony and rituals. It is also woven with the history of the peoples or ethnic communities of Kamentzá and Inga. The inhabitants of Sibundoy Valley, Putumayo Colombia show a strong influence of Eastern and other Amerindian cultures that have had a great relevance and importance on other cultures of the continent. Similarly, it treats the nature of the Indian art and aesthetics as an important aspect in the development of cosmology and the spirituality embodied in the different objects and in the aesthetics in other elements of cultural elements proper to the Kamentzá and Inga cultures.